Perancangan Sistem Penataan Arsip Berbasis Website - Sugiyamta, S; Nugroho, Isworo; Rayhan, Fahmi Fata; Sukur, Muji; Khristianto, Teguh (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Archives have an important role in an agency or company to support administrative processes or activities carried out in the company. If the archives that are owned are not managed properly, it can make it difficult to find the stored information and eventually can hinder the next process. Therefore, archives must be managed properly and properly. This study discusses how to design, implement the system and maintain and document security to avoid damage. This system was created using the PHP MySQL application. The system is built to be able to support the process of storing and retrieving the required documents in a fast and precise time